Phonon characteristics, crystal structure, and intrinsic properties of a Y(Mg1/2Sn1/2)O3 ceramic. Issue 56 (14th July 2017) - Xing, Chao; Li, Jianzhu; Chen, Huiling; Qiao, Hengyang; Yang, Jun; Dong, Helei; Sun, Haiqing; Wang, Jing; Yin, Xunqian; Qi, Ze-Ming; Shi, Feng
Abstract : Herein, a Y(Mg1/2 Sn1/2 )O3 (YMS) ceramic was synthesized using a conventional solid-state reaction method. Abstract : Herein, a Y(Mg1/2 Sn1/2 )O3 (YMS) ceramic was synthesized using a conventional solid-state reaction method. Crystal structure of YMS was investigated via X-ray diffraction (XRD). Lattice vibrational modes were obtained through Raman scattering spectroscopy and Fourier transform far-infrared (FTIR) reflection spectroscopy to study its phonon characteristics. The main phase of YMS with the monoclinic P 21 / n symmetry has been certified via XRD. The Raman active modes fitted with the Lorentzian function can be divided into three parts: vibration related to A-site Y cations, B-site (1 : 1 ordered structure of Mg 2+ : Sn 4+ ), and O ions. The eight far-infrared spectrum modes corresponded to different atomic structures of the vibration modes. Dielectric properties ( ε r and tan δ j / ω ) were deduced using the four-parameter semi-quantum model (FPSQ) and Clausius–Mossotti equation, as well as the relationship between the damping coefficient and the intrinsic loss. The imaginary and real parts of the dielectric constant were obtained via the Kramers–Krönig analysis.